2015
DOI: 10.1681/asn.2015040397
|View full text |Cite
|
Sign up to set email alerts
|

Renal 2′,3′-Cyclic Nucleotide 3′-Phosphodiesterase Is an Important Determinant of AKI Severity after Ischemia-Reperfusion

Abstract: A positional isomer of 39,59-cAMP, 29,39-cAMP, is produced by kidneys in response to energy depletion, and renal 29,39-cyclic nucleotide 39-phosphodiesterase (CNPase) metabolizes 29,39-cAMP to 29-AMP; 29,39-cAMP is a potent opener of mitochondrial permeability transition pores (mPTPs), which can stimulate autophagy. Because autophagy protects against AKI, it is conceivable that inhibition of CNPase protects against ischemia-reperfusion (IR) -induced AKI. Therefore, we investigated renal outcomes, mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…, which is produced in the kidney in response to energy depletion, and is a potent opener of apoptosis and necrosis, mediating mitochondrial permeability transition pores. 243,244…”
Section: Q35mentioning
confidence: 99%
“…, which is produced in the kidney in response to energy depletion, and is a potent opener of apoptosis and necrosis, mediating mitochondrial permeability transition pores. 243,244…”
Section: Q35mentioning
confidence: 99%
“…The function of Muc1/MUC1 in kidney has been more difficult to address as direct infection by bacteria and virus is much less common. While sepsis does stress the kidney primarily by indirect means, the most well characterized model of acute kidney injury is produced by clamping both the renal artery and vein, or the artery alone, to produce ischemia, and studying recovery of kidney function and morphology after return of blood flow for hours to days [28-30]. Using this approach, we found that Muc1 is protective in the kidney in a mouse model of ischemia-reperfusion injury by transactivation of the HIF-1 and β-catenin protective pathways [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were analyzed for 5′-AMP (immediate adenosine precursor) and adenosine by ultra-performance liquid chromatography-tandem mass spectrometry 25 . As shown in Figure 1, L-p-bromotetramisole caused a significant and sustained reduction in the renal venous levels of 5′-AMP (Figure 1A; P<0.04) and adenosine (Figure 1B; P<0.002).…”
Section: Resultsmentioning
confidence: 99%
“…5′-AMP and adenosine were quantified using ultra-performance liquid chromatography-tandem mass spectrometry, using our most recently updated version of the assay 25 .…”
Section: Methodsmentioning
confidence: 99%